2014
DOI: 10.1007/s00414-014-1017-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous methadone application as a serious risk factor for an overdose death: methadone-related fatalities in Hamburg from 2007 to 2012

Abstract: Methadone plays an increasing role in drug-related deaths in Hamburg. To find out whether intravenous application of methadone plays a relevant role in methadone-related deaths, body fluids of all methadone-positive cases (n=130) and three buprenorphine-positive cases where a urine sample was available (n=58+3) were investigated for disaccharides (sucrose and lactose as markers for intravenous methadone abuse). Sixty-four percent of the urine samples of the methadone cases showed positive results for disacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…This study of PWID in Vancouver, Canada, found that 7% of participants reported methadone injecting over the study period, and that this behavior was independently associated with both markers of socioeconomic vulnerability (homelessness, being the victim of violence) and of addiction severity/entrenchment (daily heroin injection, daily crack smoking, drug dealing, non‐fatal overdose) in multivariable analyses. Our findings of an association between non‐fatal overdose and injection of methadone are consistent with the known heightened risks of methadone injection . Interestingly, in keeping with methadone's role in addiction treatment, injection of methadone was not associated with enrollment in a methadone program after adjustment for other variables.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study of PWID in Vancouver, Canada, found that 7% of participants reported methadone injecting over the study period, and that this behavior was independently associated with both markers of socioeconomic vulnerability (homelessness, being the victim of violence) and of addiction severity/entrenchment (daily heroin injection, daily crack smoking, drug dealing, non‐fatal overdose) in multivariable analyses. Our findings of an association between non‐fatal overdose and injection of methadone are consistent with the known heightened risks of methadone injection . Interestingly, in keeping with methadone's role in addiction treatment, injection of methadone was not associated with enrollment in a methadone program after adjustment for other variables.…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that PWID are purchasing and using street methadone as a strategy to reduce heroin consumption and self‐treat opioid withdrawal symptoms. While this may be viewed as a harm reduction strategy, the risks of street methadone use on fatal overdoses have been well described previously . Similarly, as we have shown in the present study, this practice is associated with several other high‐risk behaviors.…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that PWID are purchasing and using street methadone as a strategy to reduce heroin consumption and self treat opioid withdrawal symptoms. While this may be viewed as a harm reduction strategy, the risks of street methadone use on fatal overdoses have been well described previously [9,11,18]. Similarly, as we have shown in the present study, this practice is associated with several other high-risk behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…It is not known what proportion of these deaths is related to methadone, which has been diverted; considering the frequency of OST diversion, it is possible that many of these deaths may be related to methadone diversion [17]. The role of diversion in overdose fatalities has been described in some studies: 51% of methadone overdose fatalities in Hamburg in 2007-2012 were people not in OST treatment at the time of death [18]. A study in North Carolina in 2010 reported that unintentional or undetermined drug overdoses were responsible for 892 deaths: out of the 191 deaths examined involving methadone, only 2 were patients in opioid treatment programs [19].…”
Section: Resultsmentioning
confidence: 99%